1994
DOI: 10.1128/jb.176.1.44-49.1994
|View full text |Cite
|
Sign up to set email alerts
|

GTPase-dependent signaling in bacteria: characterization of a membrane-binding site for era in Escherichia coli

Abstract: Era is an Escherichia coli GTPase that is essential for cell viability and is peripherally associated with the cytoplasmic membrane. Both immunoelectron microscopy and subcellular-fractionation experiments have shown that Era is present in cytoplasmic as well as membrane-associated pools. These data led to speculation that the mechanism of action of Era may require cycling between membrane and cytoplasmic sites. In order to investigate this possibility, an in vitro binding assay was developed to characterize t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 40 publications
1
39
1
Order By: Relevance
“…coli and S. mutans Era proteins appear to partition between the cytoplasm and the cytoplasmic membrane [15,22 -24]. The binding of Era to the membrane can be disrupted by salt treatment [15,24]. In this study, we show that a deletion of 45 residues, i.e.…”
Section: Discussionmentioning
confidence: 79%
“…coli and S. mutans Era proteins appear to partition between the cytoplasm and the cytoplasmic membrane [15,22 -24]. The binding of Era to the membrane can be disrupted by salt treatment [15,24]. In this study, we show that a deletion of 45 residues, i.e.…”
Section: Discussionmentioning
confidence: 79%
“…Immunoelectron microscopic studies localized the E. coli Era protein on the internal side of the cytoplasmic membrane and also revealed that the Era protein exists in patches on the membrane (Gollop & March, 1991a). Later, biochemical studies confirmed that the E. coli Era protein is associated with the cytoplasmic membrane (Lin et al, 1994). This association was GTP-or GDPdependent and could be disrupted by salt treatment (Lin et al, 1994).…”
Section: Introductionmentioning
confidence: 82%
“…Later, biochemical studies confirmed that the E. coli Era protein is associated with the cytoplasmic membrane (Lin et al, 1994). This association was GTP-or GDPdependent and could be disrupted by salt treatment (Lin et al, 1994). These studies led to the suggestions that potential binding sites exist on the membrane for the Era protein (Lin et al, 1994).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This situation might be artifactual and due to the histidine (and acidic residue)-rich region or might result from modifications of the protein. Possible modifications include (i) metal ions bound to the histidine-rich region, (ii) nucleotides bound to the G domains (23), and (iii) unknown groups modifying the three cysteinyl residues at the amino terminus (see above). These possibilities are currently under investigation.…”
Section: (X)-t-v-(x)-g-(x)-g-t-s-a-i-g Correspond To the Sequence Exmentioning
confidence: 99%